Strategi Komunikasi Perusahaan Umum Daerah (Perumda) Wairpu’an Kabupaten Sikka untuk Meningkatkan Produktivitas dan Kepuasan Kerja - Maria Silvana Carcia; Anastasia Krisyanti; Maria Meliani; Patricia Matilda Tina; Theresia Yunita; Mario Marianus Frengki (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
This study aims to analyze the organizational communication strategies implemented by PERUMDA Drinking Water Wairpu'an Sikka Regency in an effort to increase employee productivity and job satisfaction. Effective organizational communication is a fundamental element in building optimal performance, especially in public service companies that demand continuous cross-unit coordination. This research uses a qualitative descriptive method with data collection techniques through in-depth interviews and direct observation of company leaders and the organization's work environment. The results of the study show that PERUMDA Wairpu'an implements three main communication strategies, namely: (1) open communication through the implementation of open door policies and the implementation of regular coordination meetings; (2) clarity of the message with the use of simple, systematic language, and supported by visual media that is easy for employees to understand; and (3) speed of information delivery through early warning systems and emergency communication protocols. The implementation of this structured communication strategy has been proven to be able to create a conducive work climate, increase employee motivation and job satisfaction, and strengthen coordination and work effectiveness between units. This study recommends the development of an integrated communication system based on information technology and the implementation of effective communication training programs for all levels of the organization to support the sustainability of company performance.